Pelatihan Registrasi Google Scholar dan Sinta pada Dosen FEBI IAIN Lhokseumawe - Ismaulina Ismaulina; Sofyan Arianto (Jurnal Pengabdian Pada Masyarakat, 2020)
GOOGLE SCHOLAR AND SINTA REGISTRATION TRAINING FOR LECTURERS OF THE FACULTY OF ECONOMICS AND ISLAMIC BUSINESS OF IAIN LHOKSEUMAWE. In order to improve the quality of FEBI IAIN Lhokseumawe lecturers and the preparation of accreditation and for the sake of evicting academic levels the lecturers conducted training on google scholar account registration and Sinta Ristekdikti. The method of conducting the training is by direct demonstration, then the participants practice according to the instructions and guidelines that have been given and which have been explained by the instructor. This training provides enormous benefits for the participants because of the obligation of lecturers to input the results of publications in the Sinta portal so as to strengthen the importance of this training. At the end of the google scholar registration training and the Sinta account all trainees had a Google Scholar account and were successful in registering into the Sinta Ristekdikti portal.